STRATEGI RESOLUSI KONFLIK KELOMPOK MINORITAS; Studi Konflik Penutupan Kapel di Dau, Kabupaten Malang - Destriana Saraswati; Mohamad Anas (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
Religious conflicts in the social dynamics of society can still be found in several areas, one of which is the chapel closing event that occurred in Dau, Malang Regency. Communities in the neighborhood reject any activity or activity that using a place of worship, the Boniface Chapel. The conflict occurred as a result of a conflict between residents around the location who did not worship in the Boniface Chapel or people of other religions, and a minority group, that are local residents who worshiped in the chapel. The conflict escalated when it was forced to close and stop all activities at the chapel, since 2018 until now. There are strategic steps taken by various parties, in order to resolve the conflict. One form of conflict resolution adopted in this study is a transformation conflict and a conflict resolution strategy. This strategy will be revealed in this study using a qualitative method, a case study approach. The study began with data collection, which was carried out by means of interviews and field observations. The data that has been collected is then analyzed for presentation. The results of this study are (1) the main core forms of religious conflict in Dau, Malang Regency, and (2) conflict resolution strategies, especially those carried out by minority groups.